Identification of the Effect of Leaf Age on the Photosynthesis Rate of the Guava (Psidium guajava) - Alyasa, Rahadian Rasyid; Anjani, Nabilah; Tamasowa, Revalina Caroline; Khamilah, Risya Jheniar Nur Siti; Nilawati, Tina Safaria; Irawan, Afri (-, 2024)
The primary factor influencing photosynthesis is the presence of chlorophyll pigment. The objective of this study was conducted to identify the impact of leaf age on the rate of photosynthesis and to elucidate the correlation between the level of chlorophyll content in leaves of varying ages and the aforementioned rate. This was achieved through the utilisation of the FLDA (Floating Leaf Disk Array) method. Furthermore, the chlorophyll content measurement method was employed. The FLDA test results demonstrated that old leaves exhibited a higher rate of photosynthesis, potentially due to the elevated chlorophyll level in old leaves relative to young leaves, which averaged ±4,791 mg/ml and ±1,345 mg/ml, respectively. These findings substantiate the existence of a correlation between leaf age and the rate of leaf photosynthesis.